Migration and Metamorphosis in Marie Ndiaye's Trois Femmes Puissantes - Deborah B. Gaensbauer (Studies in 20th & 21st Century Literature, 2014)
In her 2009 Goncourt-Prize-winning novel, Trois femmes puissantes (Three Strong Women), Marie Ndiaye experiments with a polyphonic, semi-fantastical rendering of identity-threatening displacements experienced by three women from different socio-geographic backgrounds. In a brief "Counterpoint" at the end of each of the novel's three sections–a narrative take on the musical technique employed by Ndiaye to introduce new focalizations and unexpected turns of events that complicate interpretations of the characters' behavior–each of the women is perceived as metamorphosed into a bird or a birdlike persona. This essay examines the innovative embedding of the shape-shifts in Trois femmes puissantes in both harrowing socio-political realities and the ambiguities of the fantastic and superstition to convey the dehumanizing, unequal power relations governing contemporary women's migration struggles.
Keywords: Marie Ndiaye; literary fantastic; women and migration; race and identity